ANALISIS PENERAPAN GREEN ACCOUNTING PADA RUMAH SAKIT UMUM DI KOTA PADANG, SUMATERA BARAT - Novia Citra Dewi (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2017)
Hospital is a business service and one of the contributors of waste that is harmful to the environment. So hospitals need to manage the waste to be not dangerous. Management of hospital need to cost to manage the waste. The costs incurred in the management of waste are purpose to make environment not be polluted, that called as environmental costs. Environmental costs are reported in the financial statements. Therefore, we need green accounting to classify of environmental cost for make the stakeholder easy to interesting. The function is to maintain of environmental quality. Classifying of environmental costs categorized base on Hansen and Mowen. The cost is prevention of environmental cost, detection of environmental costs, internal failure of environmental costs and external failure of environmental costs. The purpose of this study are to analyze the implementation of green accounting in the public hospital in Padang, West Sumatra with using the environmental costs based on Hansen and Mowen. The data using are secondary data from the financial statements for 2014 and data on the environmental costs involves of waste treatment cost. The primary data are interviews and documentation of the condition of IPAL, Incinerator and hospital environments. The analytical methods used to analyze implementation of green accounting with using accounting treatment. There are identification, recognition, measurement, presentation and disclosure in the financial statements. The results showed that both of hospitals have not yet categorized into environmental cost as activities based on Hansen & Mowen, also not yet to disclose in the financial statements. But management hospital not realizes that the hospital already has a waste management activities and costs for environmental activities